Problematic and Marine-Coastal Zoning in Costa Rica - González, Carmen (2005)
Costa Rica has a wide marine-coastal area. This area  has  gained  more  importance  due  to  the many activities that are carried out in it and to the great tourist development. In the marine-coastal area  biophysical  aspects  together  with  human activities interact in different courses of action in time and geographical space, which have to be analyzed in an independent and careful manner. For this reason, it is necessary to develop national guidelines for a coastal regulation to be made, which must come up once basic studies to know the environment are made, and then execute the measures to develop this regulation and use it in a rational way.